Respuestas

2013-10-18T06:43:51+02:00
Solucion:
4^{x}-5(2^{x})+4=0

(2^{2})^{x}-5(2^{x})+4=0

(2^{x})^{2}-5(2^{x})+4=0   Luego aplicamos aspa simple:
 2^{x}                    -4=-4(2^{2})
 2^{x}                    -1=-1(2^{x})
                                  -5(2^{x})

---> (2^{x}-4)(2^{x}-1)=0  --->  2^{x}-2^{2}=0    v    2^{x}-1=0
                                          --->    2^{x}=2^{2}             v    2^{x}=1=2^{0}
                                             --->   x=2              v         x=0

Por tanto el C.s.= {0;2}